Measurement of The Green Waste Index Study in Bandung City - Indrawati; Fariz Indra Permana (Journal of Social Science, 2021)
The rise of population is one of the factors on the increasing amount of waste in urban area. Aside from the mentioned factor, the increase of waste also caused by changes in society consumption pattern which significantly affect the waste amount, especially in urban areas. The changes in consumption pattern shown from daily lives of urban residents, for example the habit in fast food consumption which generates garbage in the form of food container, disposable spoon and forks, and wrappers. In the City of Bandung area, to increase the effectivity in waste management, the government strengthen the waste management regulation, from home to industrial scale. Managing waste from its source is a strategic point in supporting the success of waste management. This research aims to determine Bandung green waste index, in which green waste index in a waste management concept using 3R (Reduce, Reuse, Recycle), which also an attribute of green city. This research was performed by conducting interviews to 30 respondents, screened using the quadruple helix concept: government, expert/researcher, business actors, and general society. Based on the method, this research is categorized as a mixed-method study whereupon the researcher employed both qualitative and quantitative methods. Triangulation, peer debriefing, and word association were the qualitative methods employed while validity and reliability, spearman rank, and index tabulation were the quantitative methods used. The results of the research indicate that the green waste index of city of Bandung was 72.44, which falls in the category “adequate.” The results illustrate that although the green waste management is acceptable, several aspects were still lacking. This refers to the grading scale utilized by assessors of the Indonesian Ministry of Research and Technology/National Research and Innovation (RISTEKDIKTI)